HUMAN RIGHTS DISCLOSURE ON PANDEMIC REPORTING PERIOD IN INDONESIA - Tjondro, Elisa; Sugianto, Andrew; Allan, Allan; Kusuma, Richard (Petra Christian University, 2023)
The study aims to explain the effect of the pandemic reporting period, non-executive board, audit committee, and family ownership on increasing human rights disclosure. The pandemic of COVID-19 has created an economic pandemonium globally, including in Indonesia. Indonesia's independent agency of the FSA issued a public notice in March 2020, extending the reporting period to May 2020, extending two months. This extension has created an opportunity for companies to announce their human rights practice disclosure facing the oncoming turbulent times. UNGP-BHR and the Indonesian State Law No. 39 of 1999 about Human Rights are used as the disclosure index checklist. Our study uses 345 non-financial sectors listed on the Indonesia Stock Exchange (IDX) with an observation period of 2017 - 2019. The data analysis technique is panel regression. The result shows that the pandemic reporting period, the non-executive board, and the audit committee have positively affected human rights disclosure. The 2019 annual report recorded that human rights disclosure was higher in the pandemic reporting period than in the 2017 and 2018 annual reports. This research implies that companies consider the oncoming turbulent times caused by the pandemic in disclosing last year's human rights disclosure. The non-executive board and the audit committee have a spirit of UNGPs that encourages companies to implement human rights in their operations.